Návrh technologie výroby dílů hydraulického lisu - Gryc, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Seznámení s hydraulickým lisem a popis jeho hlavních dílů. Rozbor zadaných součástí a návrh nejvhodnějšího polotovaru. Volba nástrojů a měřidel. Sestavení výrobního postupu výroby a výpočet strojních časů. Ekonomické vyhodnocení zahrnující náklady na polotovar, nářadí, mzdy dělníků a energie na provoz strojů.

An introduction of hydraulic press and description of his main parts. An analysis of the given components and a proposal for the most suitable intermediate was made. A selection of tools and gauges for individual operations has been done. A proposition of manufacturing process and enumeration of machines times was proposed. Economic evaluation containing costs for intermediate, tools, workmen’s wages and energy for operating machines has been calculated.
Suggestion of technology for manufacturing parts of a hydraulic press
Keywords: Hydraulický lis; technologie; polotovar; nástroj; vyměnitelná břitová destička; Hydraulic press; technology; intermediate; tool; indexable insert